Crisis-proof services: Why trade in services did not suffer during the 2008-2009 collapse - Andrea Ariu (European Central Bank (ECB), 2014)
During the 2008-2009 crisis trade in goods experienced the deepest decline ever recorded. Surprisingly, trade in services came through the crisis unscathed and some service categories carelessly stuck to their growth paths. Using firm-product-destination exports for Belgium, we show that the particular resilience of services is explained by a significantly lower elasticity to demand in export markets. More specifically, services exports tend to decline on average 5% less than exports of goods following a 1% decrease in GDP growth in destination countries. Most of this effect is accounted for by business services, it is more pronounced with respect to durables than to consumable products and it is stronger for OECD exports than for non-OECD. In terms of economic magnitude, if goods had the same elasticity to GDP growth of services, they would have decreased of about half. Conversely, if services had the same elasticity of goods, their fall would have been more than thrice as much.
Keywords: F10; F14; L80; 330; service resilience; services and goods trade; trade collapse